2009
DOI: 10.1039/b819720b
|View full text |Cite
|
Sign up to set email alerts
|

Protein allostery, signal transmission and dynamics: a classification scheme of allosteric mechanisms

Abstract: Classification has proven immensely important in science. Using a classification as proposed here should complement text-book descriptions and assist in understanding how function is performed on the single molecule level within the framework of its complex cellular environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
302
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(310 citation statements)
references
References 52 publications
(73 reference statements)
4
302
1
3
Order By: Relevance
“…Allostery (Tsai et al, 2009;Tsai and Nussinov, 2014;Liu and Nussinov, 2016) is a mode of long-distance communication between distal sites in proteins, in which the energy released as a consequence of conformational or dynamic changes at one site can travel along specific pathways within the protein structure to other sites, changing their conformational or dynamic properties (Liu and Nussinov, 2017). Computational methods directly relating protein structural dynamics to information exchange between functional sites have also been devised (Lenaerts et al, 2008).…”
Section: Rri As Allosteric Interactionsmentioning
confidence: 99%
“…Allostery (Tsai et al, 2009;Tsai and Nussinov, 2014;Liu and Nussinov, 2016) is a mode of long-distance communication between distal sites in proteins, in which the energy released as a consequence of conformational or dynamic changes at one site can travel along specific pathways within the protein structure to other sites, changing their conformational or dynamic properties (Liu and Nussinov, 2017). Computational methods directly relating protein structural dynamics to information exchange between functional sites have also been devised (Lenaerts et al, 2008).…”
Section: Rri As Allosteric Interactionsmentioning
confidence: 99%
“…Our work bears some relationship to certain diseases caused by mutations that induce allosteric effects (2,39). These can shut down the functionality of allosteric enzymes, or they can cause conformational changes at the active site that lead to constitutive activation regardless of whether an effector is bound, as in the case of the G-protein (2).…”
Section: Discussionmentioning
confidence: 99%
“…allosteric effects | enzymes | molecular dynamics simulations | protein engineering P rotein allostery has been recognized as a positive or negative cooperative event, leading to a structural change at the binding site as a result of distal docking of a molecule acting as an effector (1)(2)(3)(4)(5). Allosteric effects can be influenced by such factors as variation in pH, temperature, ionic strength, and covalent modification as well as mutational changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a variety of allosteric reactions demonstrate that such a contiguous pathway is not necessary, nor does a net conformational change always occur with agonist binding. To account for these results, it has been suggested that changes in dynamics with allosteric binding are responsible for the changes to substrate binding constants or promoter binding (Bhabha et al 2013;Boehr et al 2013;Gunasekaran et al 2004;Nussinov and Tsai 2013;Tsai et al 2009). Long-range structural vibrations, often referred to as the collective vibrational modes, or global vibrations, readily provide a mechanism to correlate motions between distant regions.…”
Section: Introduction: Long-range Vibrations and Allosterymentioning
confidence: 99%